Application of Differential Scanning Calorimetric Method for Assessing and Monitoring Various Physical and Oxidative Properties of Vegetable Oils - Tan, Chin Ping (2001)
Differential scanning calorimetry (DSC) can be a powerful instrumental technique for analyzing oils and fats systems but has tended not to be well understood and used in the field of oils and fats. The main purpose of this project is to develop various techniques based on DSC to study the physical and chemical properties of vegetable oils. High-performance liquid chromatography (HPLC), gas-liquid chromatography (OLC), oxidative stability instrument (OS1), and various standard chemical analyses were used in this investigation to complement the DSC methods. This work is a systematic study of vegetable oils' melting and crystallization profiles by using DSC. The investigation began with the successful comparison of the DSC thermal curves of 17 different vegetable oils. Thorough investigations in this work were also directed towards obtaining basic information about the relationship between thermal profiles and chemical compositions of 17 different vegetable oils. Thereafter, the effects ofDSC scanning rate variation were studied. Scanning rates were found to affect melting/crystallization profile, melting (and/or crystallization) offset (and/or onset) and peak. temperatures, and peak. enthalpies of all vegetable oils. In this study, DSC was utilized to monitor the oxidation of heated oils during deep-fat frying and microwave heating. A statistical comparative study was carried out on the DSC and standard chemical methods. The results revealed that there is good correlation (P < 0.01) between the DSC method and other standard chemical methods. In another study, a new calorimetric technique was developed to determine three important quality indices in deep-fat frying industry namely, total polar compounds (TPC), free fatty acid (FFA) content and iodine value (IV) of heated oils using the DSC cooling profiles. The studies have shown that all DSC methods developed were comparable to the standard American Oil Chemists' Society (AOCS) methods. A simple and efficient DSC technique to determine the oxidative stability of vegetable oils was described. The isothermal DSC technique for direct determination of the oxidative stability of vegetable oils has been built and a comparative study to OSI was demonstrated. The results indicated that there is good correlation (P < 0.01) between the DSC oxidative induction time (To) and OSI values. Isothermal calorimetry was then employed as a general analytical method where the Arrhenius kinetic data for the lipid oxidation of vegetable oils were obtained by measurement of the DSC To at various temperatures. The present study also developed a simple method for measuring the antioxidant activity in RBDPOo using isothermal DSC technique. Generally, this project concluded that DSC appears to be a useful method in determining various physical and chemical parameters of vegetable oils, and it may have the potential to replace the laborious, time- and chemical-consuming standard methods. The various methods developed here can be applied in the oils and fats industry.